2009
DOI: 10.1128/cvi.00044-09
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Active Tuberculosis in China Using an In-House Gamma Interferon Enzyme-Linked Immunospot Assay

Abstract: Gamma interferon (IFN-␥) release assays have been proven to be useful in the diagnosis of 5%). In conclusion, the IFN-␥ ELISPOT assay is a useful adjunct to current tests for diagnosis of active TB in China. The ELISPOT assay is more accurate than TST in identifying TB infections.Tuberculosis (TB) is a leading cause of morbidity and mortality throughout the world, with 95% of cases and 97% of all deaths occurring in high-prevalence countries, such as China, where the prevalence of active TB is as high as 367/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 14 publications
4
65
0
Order By: Relevance
“…Due to the shortage of available methods for diagnosis of TB, IGRAs have increasingly been used as an auxiliary diagnostic tool for active TB in clinical practice in China (18,(31)(32)(33). Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the shortage of available methods for diagnosis of TB, IGRAs have increasingly been used as an auxiliary diagnostic tool for active TB in clinical practice in China (18,(31)(32)(33). Indeed, it has been reported that detection of IFN-␥ in pleural fluid mononuclear cells is useful for diagnosis of tuberculous pleurisy (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 16 healthy controls (HC) and 33 subjects with LTBI were recruited from household contacts of active TB patients, all of whom had no evidence of disease or history of TB. A previously described in-house M. tuberculosis antigen-specific IFN-␥ enzyme-linked immunosorbent spot (ELISPOT) assay was used to diagnose LTBI (17,18). The detailed clinical characteristics of patients are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnosis also included clinical signs and symptoms and radiographic findings (chest x-ray and/or HRCT) (20). All recruited individuals were also examined for antigenspecific IFN-␥ secretion using a well-established ELISPOT kit (21). Patients determined to be positive based on bacteriological examination were recruited for a second or third round of experiments to identify antigenicity.…”
Section: Methodsmentioning
confidence: 99%
“…Cellular Antigen-specific IFN-␥ ELISPOT Assay-An IFN-␥ ELISPOT assay was performed using a human IFN-␥ cytokine precoated ELISPOT kit (Dakewe Biotech Company, Shenzhen, China) as previously described (21). Briefly, the plates were seeded with 2.5 ϫ 10 5 freshly separated PBMCs per well.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the QFT-IT assay was used to detect LTBI, and only QFT-IT assay-negative subjects were included as healthy controls; this could lead to an overassessment of QFT-IT assay specificity. Considering the high prevalence of TB infection in China, LTBI can be detected even in low-risk communities (33,34). Thus, one cannot exclude the possibility that the one healthy control that appeared to generate a falsepositive response to the combination of Rv1985c pool2 and Rv1985c pool4 might represent an individual with a true LTBI that was missed with the QFT-IT test.…”
Section: Differentiation Of M Tuberculosis Infection In Bcg-vaccinatedmentioning
confidence: 99%